2019
DOI: 10.3390/molecules24173190
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Tebuconazole Influences the Structure of Human Serum Albumin Molecule

Abstract: Studies of interactions between pesticides and target mammalian proteins are important steps toward understanding the pesticide′s toxicity. Using calorimetric and spectroscopic methods, the interaction between triazole fungicide tebuconazole and human serum albumin has been investigated. The spectroscopic techniques showed that fluorescence quenching of human serum albumin by tebuconazole was the result of the formation of tebuconazole/human serum albumin complex with the static type as the dominant mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Albumin is not just passive, but an active participant in pharmacokinetic and toxicokinetic processes too. The esterase or pseudoesterase activity of albumin against α-naphthyl acetate and p -nitrophenyl acetate (NPA), FA esters, aspirin, ketoprofen glucuronide, cyclophosphamide, nicotinic acid esters, octanoyl-ghrelin, nitroacetanilide, p -nitrofluoroacetanilide and some OPs have been demonstrated in numerous experiments [ 56 , 66 , 67 , 68 ]. A typical example of the pseudoesterase activity of albumin is acetylation.…”
Section: Enzymatic Activity Of Albuminmentioning
confidence: 99%
“…Albumin is not just passive, but an active participant in pharmacokinetic and toxicokinetic processes too. The esterase or pseudoesterase activity of albumin against α-naphthyl acetate and p -nitrophenyl acetate (NPA), FA esters, aspirin, ketoprofen glucuronide, cyclophosphamide, nicotinic acid esters, octanoyl-ghrelin, nitroacetanilide, p -nitrofluoroacetanilide and some OPs have been demonstrated in numerous experiments [ 56 , 66 , 67 , 68 ]. A typical example of the pseudoesterase activity of albumin is acetylation.…”
Section: Enzymatic Activity Of Albuminmentioning
confidence: 99%
“…Such hydrophobic spaces may be occupied by the hydrophobic regions of the TB molecule associated with the tert-butyl substituent. The possibility of this type of interactions was confirmed in the above-mentioned studies on TB docking to CYP51 and human serum albumin [50,51], and was suggested by many other authors [16,17,26,27].…”
Section: Mechanisms Of Tb Adsorption On Som and Clay Mineralsmentioning
confidence: 52%
“…Moreover, there is also the possibility of π-π interactions of aromatic rings. The existence of such interactions was also indicated in previous studies on TB docking to the active sites of the CYP51 enzyme and the human serum albumin [50,51]. It seems that the formation of hydrogen bonds can be the dominant type of interaction of TB molecule in more polar regions of SOM with numerous functional groups (-OH, =C=O, =NH, or -NH 2 ).…”
Section: Mechanisms Of Tb Adsorption On Som and Clay Mineralsmentioning
confidence: 53%
“…The binding constants K a were calculated by the double logarithm equation (log[( F 0 / F )/ F ] ~ log[Q]) as show in Figure 9 49 logF0F/F=logKa+nlognormalQ. …”
Section: Resultsmentioning
confidence: 99%